Should All Research Subjects Be Treated the Same? - Brody, Baruch; Migueles, Stephen A.; Wendler, David (Hastings Center Report, 2015)
One of the founding principles of research ethics is that subjects should be treated equally. In the words of the Belmont Report, 'equals ought to be treated equally.' This principle does not imply that all subjects should be treated exactly the same. Rather, subjects who are similar in relevant respects should receive similar treatment. Clinical status is clearly relevant to determining how subjects should be treated. Greater resources should be devoted to subjects who have worse diseases. In contrast, fame is irrelevant. Subjects should not receive greater resources simply because they are famous. A more challenging question, one that pervades clinical research yet has received almost no attention in the literature, is whether subjects' level of scientific importance is relevant to determining how much support they should receive..